RESEARCH ON ESTIMATION OF UNIAXIAL CONSTITUTIVE RELATIONSHIP OF METAL MATERIAL BY SMALL PUNCH TEST OF STRIP-TYPE SPECIMEN - LIU Gang; GUAN KaiShu; ZHONG JiRu; WANG WuLin (Jixie qiangdu)
The empirical correlation method of small punch test is the main method to obtain the mechanical properties of macroscopic materials. However,owing to the empirical correlation method is limited by the test device of small punch test and the size of specimen,there is no unified and recognized empirical correlation formula so far. In order to obtain the semi-analytical solution formula by using the small punch test,a new strip-type specimen of small punch test based on the energy equivalence principle and the finite element analysis method were adopted to obtain 4 coefficients of the Chen-Cai semi-analytical equation. A new method of estimating the uniaxial constitutive relationship of metal material by small punch test of strip-type specimen was proposed. The uniaxial constitutive relationship of Q345 R steel and 904 stainless steel estimated by the new method is in good agreement with the true stress-strain curve obtained by uniaxial tensile test.